Usability and feasibility of a cognitive-behavioral mobile app for ADHD in adults - Laura E. Knouse; Xiaodi Hu; George Sachs; Sebastian Isaacs (PLOS Digital Health, 2022)
Objective Cognitive-behavioral therapy (CBT) has growing evidence of efficacy for Attention-Deficit/Hyperactivity Disorder (ADHD) in adults. Mobile health apps are promising tools for delivering scalable CBT. In a 7-week open study of Inflow, a CBT-based mobile app, we assessed usability and feasibility to prepare for a randomized controlled trial (RCT). Method 240 adults recruited online completed baseline and usability assessments at 2 (n = 114), 4 (n = 97) and after 7 weeks (n = 95) of Inflow use. 93 participants self-reported ADHD symptoms and impairment at baseline and 7 weeks. Results Participants rated Inflow’s usability favorably, used the app a median of 3.86 times per week, and a majority of those using the app for 7 weeks self-reported decreases in ADHD symptoms and impairment. Conclusion Inflow demonstrated usability and feasibility among users. An RCT will determine whether Inflow is associated with improvement among more rigorously assessed users and beyond non-specific factors. Author summary Attention-Deficit Hyperactivity Disorder (ADHD) is characterized by frequent and impairing inattention and/or hyperactivity/impulsivity that begins in childhood and sometimes continues to cause problems into adulthood. While some medications are helpful in treating ADHD, medications do not work for everyone and some adults continue to experience ADHD symptoms even with medication treatment. Cognitive-behavioral therapy (CBT) helps people learn skills to better manage their actions and thoughts. Face-to-face CBT for adult ADHD has shown promising results in some studies, but this treatment can be hard for people to access. Mobile apps are promising tools for delivering CBT to more people in their daily lives but only one previous study has examined a CBT-based app for adults with ADHD. To prepare for a larger controlled study, we gathered data from participants who used Inflow, a CBT-based mobile app, for 7 weeks. We recruited 240 adults online, gave them access to the app, and asked those who downloaded it (n = 205) to complete assessments after 2, 4, and 7 weeks. Participants rated Inflow as user-friendly and we learned more about how often people use they app and which features they access. A majority of the people who stayed in the study after 7 weeks (n = 93) rated their ADHD symptoms as less severe than when they started the study. Next, we need to conduct a randomized, controlled study to better evaluate whether these changes are really due to the effects of Inflow.